2018
DOI: 10.1039/c8nj01078a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of core–shell structured M@Pd/SnO2–graphene [M = Co, Ni or Cu] electrocatalysts for ethanol oxidation in alkaline solution

Abstract: Core–shell structured M@Pd/SnO2–graphene (Gr), [M = Co, Ni or Cu] electrocatalysts were synthesized using ethylene glycol as a reducing agent with the aid of microwave irradiation in a two-step process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…For example, Pd/FeO x (OH) 2‐2x nanoparticles displayed relatively superior HER activity to Pd/Fe 3 O 4 core/shell nanoparticles [13]. Pd 3 d deconvolution of the nanocatalysts (Figure 5g and 5 h) give doublet splitting at binding energies of 335.6 (Pd 3 d 5/2 ) and 341.0 eV (Pd 3 d 3/2 ), which are described as mixed metallic Pd and PdO x , shown in the inset at lower additional spectral fitting [40].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Pd/FeO x (OH) 2‐2x nanoparticles displayed relatively superior HER activity to Pd/Fe 3 O 4 core/shell nanoparticles [13]. Pd 3 d deconvolution of the nanocatalysts (Figure 5g and 5 h) give doublet splitting at binding energies of 335.6 (Pd 3 d 5/2 ) and 341.0 eV (Pd 3 d 3/2 ), which are described as mixed metallic Pd and PdO x , shown in the inset at lower additional spectral fitting [40].…”
Section: Resultsmentioning
confidence: 93%
“…For example, Pd/FeO x (OH) 2-2x nanoparticles displayed rela-tively superior HER activity to Pd/Fe 3 O 4 core/shell nanoparticles [13]. Pd 3d deconvolution of the nanocatalysts (Figure 5g and 5 h) give doublet splitting at binding energies of 335.6 (Pd 3d 5/2 ) and 341.0 eV (Pd 3d 3/2 ), which are described as mixed metallic Pd and PdO x , shown in the inset at lower additional spectral fitting [40]. Figure 6 indicates the TEM micrographs of the Nibased composites and nanocatalysts with particles distributions (inset) in the Ni/MOFDC (Figure 6a) and AT-Ni/ MOF (Figure 6b) having lattice distances of 0.277 and 0.561 nm, and mean particle sizes of 13.7 and 11.6 nm, respectively.…”
Section: Full Papermentioning
confidence: 93%
“…Electron transfer from WC to Pd in the nanocomposites not only modifies the electronic structure of the Pd domain,w hich is favorable for the scission of ethanol molecules on Pd sites, but also weakenst he adsorption of poisoning intermediates, such as CO, on the Pd surface by increasing the electron density around Pd atoms. [238] The M@Pd/SnO 2 -Gr nanocomposites exhibit ag radualn egative shift of their Pd (111) Therefore, intermediate CO specieso nP ds ites formed duringt he EOR can be removed in at imely manner by adjacent ÀOH active species on the WC domains through ab ifunctional mechanism [200,214] or the hydrogen spillover effect.…”
Section: Noble-metal-based Composite Nanocatalysts For the Eormentioning
confidence: 99%
“…In ar ecent study,F ahim et al reported the synthesis of nanocomposites consisting of core-shellstructured M@Pd (M = Co, Ni or Cu) and SnO 2 -graphene, labeled as M@Pd/SnO 2 -Gr,w hich combined the advantages of core-shell geometry with the features of composite nanomaterials, in at wo-step process with ethylene glycol as ar educing agent and the assistance of microwave irradiation. [238] The M@Pd/SnO 2 -Gr nanocomposites exhibit ag radualn egative shift of their Pd (111) [213].Copyright 2013, American Chemical Society. ChemSusChem 2019ChemSusChem , 12,2117ChemSusChem -2132 www.chemsuschem.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim metal-based nanocomposites,aswell as their ligand and/orensemble effects, further enhancement in the electrocatalytic performance for the EOR could expected.…”
Section: Noble-metal-based Composite Nanocatalysts For the Eormentioning
confidence: 99%
“…Copper oxides have attracted particular attention, with a number of studies showing that they can improve catalytic activity and adsorption properties (Giziński et al, 2020;El Attar et al, 2021). Previous studies investigated the catalytic activities of Cu as a base (Wu et al, 2017;Fahim et al, 2018) and as a component in multicomponent catalysts (Freitasa et al, 2014;Almukhlifia and Burns, 2015;Oznuluer et al, 2018). A number of studies showed that metal oxides copper (I) oxide -an inorganic compound (Cu2O) and copper (II) oxide -an inorganic compound (CuO) fixed on the surface of a copper (0) (Cu) electrode (CE) exhibited excellent electrocatalytic activity and stability (Sato et al, 2012;Wan, 2013;Gao et al, 2018;Scherzer, 2019).…”
Section: Introductionmentioning
confidence: 99%